2013
DOI: 10.1080/13803395.2013.806650
|View full text |Cite
|
Sign up to set email alerts
|

Age-related change in Wechsler IQ norms after adjustment for the Flynn effect: Estimates from three computational models

Abstract: A previous study found that the Flynn effect accounts for 85% of the normative difference between 20- and 70-year-olds on subtests of the Wechsler intelligence tests. Adjusting scores for the Flynn effect substantially reduces normative age-group differences, but the appropriate amount of adjustment is uncertain. The present study replicates previous findings and employs two other methods of adjusting for the Flynn effect. Averaged across models, results indicate that the Flynn effect accounts for 76% of norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…These issues were addressed by Kaufman (2010), who pointed out that changes in the instructions and content of specific Wechsler subtests (e.g., Similarities) could make comparing older and newer versions akin to comparing apples and oranges. However, other research has shown that estimates of the size of the Flynn effect based on changes in subtest scores yield values similar to estimates from the composite scores (Agbayani & Hiscock, 2013;Dickinson & Hiscock, 2010). Kaufman's concern related to interpretations of the basis of the Flynn effect and not to its existence, and we did not pursue this question because it has been addressed in other studies (Dickinson & Hiscock, 2011).…”
Section: The Current Studymentioning
confidence: 77%
“…These issues were addressed by Kaufman (2010), who pointed out that changes in the instructions and content of specific Wechsler subtests (e.g., Similarities) could make comparing older and newer versions akin to comparing apples and oranges. However, other research has shown that estimates of the size of the Flynn effect based on changes in subtest scores yield values similar to estimates from the composite scores (Agbayani & Hiscock, 2013;Dickinson & Hiscock, 2010). Kaufman's concern related to interpretations of the basis of the Flynn effect and not to its existence, and we did not pursue this question because it has been addressed in other studies (Dickinson & Hiscock, 2011).…”
Section: The Current Studymentioning
confidence: 77%
“…The advantage of older over younger adults of 1.6/20 aMH points remained stable across 16 years, with a linear decrease in vocabulary scores for both groups. Note that the analysis did not involve adjustments to counteract the Flynn effect (Agbayani & Hiscock, 2013; Dickinson & Hiscock, 2010) because the effect typically does not involve crystallized intelligence factors such as vocabulary (Flynn, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Age‐scaled scores for all the EF measures were used for analyses, thus age was not included as a covariate. Previous neuropsychological research suggests that statistically controlling for age is unnecessary when using age‐adjusted standard scores (Agbayani & Hiscock, ; Salthouse, ). Minority status was coded as 0 = Caucasian and 1 = non‐Caucasian (African‐American, Hispanic/Latina, Asian or multiracial).…”
Section: Methodsmentioning
confidence: 99%
“…Agescaled scores for all the EF measures were used for analyses, thus age was not included as a covariate. Previous neuropsychological research suggests that statistically controlling for age is unnecessary when using age-adjusted standard scores (Agbayani & Hiscock, 2013;Salthouse, 2013 there is a strong positive correlation between years of education and IQ (Lange et al, 2010;Matarazzo & Herman, 1984). In addition, there is there is an overlap in measures of fluid intelligence tests and working memory and processing speed tasks, due to the memory maintenance required on fluid intelligence tests (Conway, Cowan, Bunting, Therriault & Minkoff, 2002;Fry & Hale, 1996;Little, Lewandowsky & Craig, 2014).…”
Section: Data Analytic Planmentioning
confidence: 99%